2007
DOI: 10.1136/ard.2006.068502
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility of myositis autoantibody testing for predicting the risk of cancer-associated myositis

Abstract: Objectives: There is a known association between myositis and cancer. The risk is greater in dermatomyositis (DM) than polymyositis (PM), although reliable methods to predict cancer risk in specific patients with myositis are not presently available. This study was undertaken to determine whether risk of developing cancer in myositis can be predicted by antibody profiling. Methods: A cross-sectional study of UK Caucasian adults with PM (n = 109), DM (n = 103) and connective tissue disease overlap (myositis/CTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
2
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(224 citation statements)
references
References 23 publications
11
193
2
18
Order By: Relevance
“…It was demonstrated that antigenic myositis-specific autoantigens are expressed in both tumor cells and myoblasts, and then myositis-specific autoantigen is expressed in an initial tumor leading to the generation of both specific T and B cells targeting those antigens, and subsequently stimulate immune responses previously generated in the anti-tumor response. [12][13][14][15] These may explain the mechanism of the coexistence of DM and cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that antigenic myositis-specific autoantigens are expressed in both tumor cells and myoblasts, and then myositis-specific autoantigen is expressed in an initial tumor leading to the generation of both specific T and B cells targeting those antigens, and subsequently stimulate immune responses previously generated in the anti-tumor response. [12][13][14][15] These may explain the mechanism of the coexistence of DM and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…16 Thus, the determination of clinical and laboratory signs for association with malignancy are of great importance for the disease prognosis. In some studies, relatively high proportions of anti-155/140 antibodies were detected in cancer-associated DM patients, and these have an excellent positive predictive value 12,13,17 Therefore, introduction of a commercial kit for this antibody to be applied in clinical screening may be beneficial. It was also shown that anti-Jo-1 antibody and cancer-associated DM, or interstitial lung disease and cancerassociated DM appear mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional use of MTX showed significantly improved treatment efficacy. A previous study by Chinoy et al examined the risk of cancer-associated myositis (25). They showed that the detection of anti-Ku antibody in myositis is associated with a lower frequency of cancer as well as a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis, factors associated with a paraneoplastic etiology of myositis include advanced age, male gender, skin necrosis, and dysphagia [104]. Detection of anti-155/140-Abs in cases with negative classical Abs (anti-Jo-1, anti-PM-Scl, anti-U1-RNP, anti-U3-RNP, anti-Ku) is in 94 % associated with a paraneoplastic origin [105]. While anti-synthetase-Abs are typically associated with autoimmune etiology, their detection does not reliably rule out a paraneoplastic origin of the disease [106].…”
Section: Paraneoplastic Myositismentioning
confidence: 99%